1999
DOI: 10.1074/jbc.274.12.8322
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation by the Bacillus subtilis GerE Protein

Abstract: GerE is a transcription factor produced in the mother cell compartment of sporulating Bacillus subtilis. It is a critical regulator of cot genes encoding proteins that form the spore coat late in development. Most cot genes, and the gerE gene, are transcribed by K RNA polymerase. Previously, it was shown that the GerE protein inhibits transcription in vitro of the sigK gene encoding K . Here, we show that GerE binds near the sigK transcriptional start site, to act as a repressor. A sigK-lacZ fusion containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…Transcription of a cotD-lacZ fusion is sevenfold higher in the wild type than in a gerE mutant (20). Our microarray results showed that whereas AWS144 (wild-type) RNA had cotD transcript at a 7.72-fold-higher level than the reference RNA, AWS133 (citB5 mutant) had cotD transcript at only a 1.12-foldhigher level than the reference.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Transcription of a cotD-lacZ fusion is sevenfold higher in the wild type than in a gerE mutant (20). Our microarray results showed that whereas AWS144 (wild-type) RNA had cotD transcript at a 7.72-fold-higher level than the reference RNA, AWS133 (citB5 mutant) had cotD transcript at only a 1.12-foldhigher level than the reference.…”
Section: Resultsmentioning
confidence: 81%
“…Our microarray results showed that the sigK (spoIVCB) transcript was 3.33-fold more abundant in AWS133 (citB5 mutant) than in the reference RNA, while in AWS144 (wild type), spoIVCB was 1.44-fold more abundant than in the reference RNA. This result is reminiscent of the phenotype of a gerE mutant, which has twofold-higher sigK-lacZ expression than does the wild type (20). Since GerE-dependent repression of sigK inhibits accumulation of K during late stages of sporulation (20), we performed immunoblotting to analyze K levels in the wild-type strain and in AWS133.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations